Formação de professores de educação física para inclusão educacional usando tecnologia assistiva - Toloi, Gabriela Gallucci [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Physical Education classes, by being constituted with a great diversity of programmatic context that belonging to the area, make the teacher feel the need to establish teaching strategies and select pedagogical resources suitable and/or adaptable activities that students can be able to perform the various activities proposed. However, the normal teaching sequence during classes doesn't seem to be as smooth as usual when a teacher faces students with some kind of disability, especially in a regular school. This situation is often linked to lack of knowledge on how to handle these special students, in other words, the proper formation of the teachers is a factor that seems to be a problem already encountered, which means that teachers need a deeper knowledge on how to handle, teach and choose activities for this population. In this sense, the goal of this research was to plan, implement and evaluate a training program for Physical Education Teachers having focused the inclusive education of students with disabilities through access of Assistive Technology. This research was divided in four studies: a) Study 1, sought to identify the difficulties mentioned by the Physical Education Teachers while working with students with disabilities, and the instrument used to collected the data was a focus group (FG) with the Physical Education Teachers in the city of Bauru; b) Study 2, pursue to characterize the context of Physical Education classes, evaluating a practice of one PE teacher and also his actions dealing with a inclusion; to record the data the instrument used was a videotaped; c) Study 3, was structured in planning and executing the theoretical classes for the PE teachers focusing on actions concerning the difficulties named and found during the FG; to collect the data an instrument was developed using the Likert scale to self-analyze their knowledge before and after classes; d) Study 4, seek to analyze an intervention based on a...

As aulas de Educação Física, por serem constituídas de grande diversidade nos conteúdos programáticos pertencentes à área, fazem com que o professor necessite estabelecer estratégias de ensino e selecionar recursos pedagógicos adequados e/ou adaptados para que seu alunado desempenhe, adequadamente, as várias atividades propostas. No entanto, esse transcurso normal das aulas parece não ser tão tranquilo quando o professor defronta-se com alunos com deficiência, principalmente no ensino regular. Essa situação muitas vezes se atrela ao desconhecimento de como lidar com esses alunos, ou seja, o fator formação parece ser um problema encontrado, o que faz com que os professores necessitem de conhecimento mais aprofundado sobre como lidar, ensinar e escolher atividades para essa população. Nesse sentido, o objetivo deste trabalho foi planejar, aplicar e avaliar um programa de formação para professores de Educação Física, visando à inclusão educacional de alunos com deficiência, por meio do acesso aos recursos de Tecnologia Assistiva. Para tal, dividiu-se o trabalho em 4 estudos: a) Estudo 1, que buscou identificar as dificuldades relatadas pelos professores de Educação Física ao trabalhar com alunos com deficiência em aulas inclusivas; a coleta de dados foi realizada através do Grupo Focal (GF) com os professores de Educação Física do município de Bauru; b) Estudo 2, que procurou caracterizar o contexto das aulas de Educação Física, provindas da prática do professor e também suas ações junto à inclusão escolar, utilizou-se como forma de registro a filmagem das aulas; c) Estudo 3, que buscou avaliar as aulas teóricas planejadas para um curso de formação continuada oferecido aos professores de Educação Física, como instrumento de coleta dos dados foi criado uma ficha de auto avaliação usando-se a escala Likert; d) O Estudo 4, que procurou analisar uma...
Keywords: Professores - Formação; Educação inclusiva; Educação especial; Educação - Estudo e ensino; Equipamentos de autoajuda para deficientes; Inclusive education